Epic Stone Butch transmasculinity in the work of Willa Cather - Hammer, K. Allison (Transgender Studies Quarterly, 2020)
Through application of the contemporary term transmasculinity and the more historical stone butch, the author questions the critical tendency to perceive American writer Willa Cather only as lesbian while ignoring or undertheorizing a transgender longing at play in her fiction, short stories, and letters. While biographical evidence must not be approached as simply coterminous with literary production, as literature often exceeds or resists such alignments, Cather's letters in particular suggest a strong identification with her male fictional alliances. Analysis of her letters alongside two of her most treasured, and disparaged, novels, One of Ours (1922) and The Professor's House (1925), conveys Cather's wish for an idealized masculinity, both for herself and for Western culture, that would survive two coeval historical processes and events: the closing of the American frontier and the First World War. Through what the author calls a stone butch “armature,” she and her characters retained masculine dignity despite historical foreclosure of Cather's manly ideal, Winston Churchill's Great Man, who was for her the artistic and intellectual casualty of the period. Cather expressed the peculiar nostalgic longing present in stone butch, and in the explosion of new forms of transmasculinity in the present. This suggests that historical transgender styles don't disappear entirely, even as new categories emerge.
Keywords: 1900-1999; 1910-1919; 1920-1929; amériques; approches et analyses; arts; butch; discipline; identités LGBTQIA2+; personnes trans*; périodes historiques; queer; régions géographiques; états-unis; études littéraires

Radclyffe Hall: A life in the writing - Dellamora, Richard (Haney Foundation series, 2011)
The Well of Loneliness is probably the most famous lesbian novel ever written, and certainly the most widely read. It contains no explicit sex scenes, yet in 1928, the year in which the novel was published, it was deemed obscene in a British court of law for its defense of sexual inversion and was forbidden for sale or import into England. Its author, Radclyffe Hall, was already well-known as a writer and West End celebrity, but the fame and notoriety of that one book has all but eclipsed a literary output of some half-dozen other novels and several volumes of poetry. In Radclyffe Hall: A Life in the Writing Richard Dellamora offers the first full look at the entire range of Hall's published and unpublished works of fiction, poetry, and autobiography and reads through them to demonstrate how she continually played with the details of her own life to help fashion her own identity as well as to bring into existence a public lesbian culture. Along the way, Dellamora revises many of the truisms about Hall that had their origins in the memoirs of her long-term partner, Una Troubridge, and that have found an afterlife in the writings of Hall's biographers. In detailing Hall's explorations of the self, Dellamora is the first seriously to consider their contexts in Freudian psychoanalysis as understood in England in the 1920s. As important, he uncovers Hall's involvement with other modes of speculative psychology, including Spiritualism, Theosophy, and an eclectic brand of Christian and Buddhist mysticism. Dellamora's Hall is a woman of complex accommodations, able to reconcile her marriage to Troubridge with her passionate affairs with other women, and her experimental approach to gender and sexuality with her conservative politics and Catholicism. She is, above all, a thinker continually inventive about the connections between selfhood and desire, a figure who has much to contribute to our own efforts to understand transgendered and transsexual existence today.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; discipline; europe; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; royaume-uni; régions géographiques; thématiques; études littéraires

Mrs Dalloway - Woolf, Virginia (Collection Folio classique, 1994)
Dans son quatrième roman, Mrs Dalloway (1925), l'écrivaine anglaise Virginia Woolf aborde le sujet des classes moyennes anglaises au lendemain de la guerre de 1914-18. Elle a noté dans son journal qu'elle voulait « donner la vie et la mort, la santé mentale et la folie ; Je veux critiquer le système social, & le montrer à l'œuvre, à son plus intense'. La forme, ainsi que le contenu du roman est essentiellement "moderne". La technique pionnière du "flux de conscience" de Woolf reflétait son désir de montrer la nature multiforme de la conscience et de capturer l'impact du monde moderne en évolution rapide sur la psyché. Un récit onirique transporte le lecteur à travers une ville surpeuplée et dans l'esprit de différents individus isolés : nous nous concentrons particulièrement sur Mme Clarissa Dalloway, une dame de la société d'âge moyen et Septimus Warren Smith, un jeune soldat démobilisé en état de choc. Comme dans Ulysses (1922) de James Joyce , l'action se limite principalement à une journée ; dans ce cas en juin 1923. Le roman commence par la phrase "Mme Dalloway a dit qu'elle achèterait les fleurs elle-même" alors qu'elle passe la journée à préparer une fête, et se termine par la fête qui se déroule le soir, alors qu'elle apprend au passage le suicide de Septimus. Néanmoins, le livre nous sort de tout cadre temporel strict en incorporant des moments de réminiscence d'un certain nombre de personnages. Du passé de Septimus, nous apprenons que sa classe sociale l'a empêché d'aller à l'université ; il était « l'un de ces hommes semi-éduqués et autodidactes dont toute l'éducation est apprise dans des livres empruntés aux bibliothèques publiques », et son désir d'être poète l'a finalement conduit à s'enrôler dans l'armée, comme pour défendre un shakespearien idéalisé. Angleterre. Le traitement par Woolf des soins psychiatriques qu'il reçoit - Septimus se tue lorsqu'il apprend qu'il est interné dans un sanatorium - semble s'appuyer sur sa propre expérience de la maladie mentale. Les regrets plus doux de la classe supérieure et le sentiment d'isolement de Mme Dalloway fournissent une sorte de contre-rythme. Sa fille, Elizabeth, est inévitablement le symbole de la jeune femme de Clarissa, et elle se souvient des chemins amoureux et de la vie qu'elle n'a pas empruntés par son ancien prétendant Peter Walsh et par Sally Seton, qu'elle a embrassé une fois, mais qu'elle a maintenant épousé. un homme d'affaires provincial. Le roman est devenu l'une des œuvres les plus célèbres de Woolf et l'un des textes déterminants du modernisme littéraire.
Keywords: 1900-1999; 1910-1919; 1920-1929; arts; cours; discipline; europe; fem5050; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; écriture des femmes*; études littéraires

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires